PENINGKATAN KEPERCAYAAN DIRI MELALUI KEGIATAN MENARI KREATIF - HERMAYANTI, TITIN (Jurnal Pendidikan Usia Dini, 2015)
Abstract: The purpose of this research was to determinate the proccess of implementation creation dance to increase self confidence in Group B Satu Atap Kramat Jati 25, East Jakarta. This research is an action research which refers to the model of a classroom Action Research Kemmis and Mc. Taggart. The subject of this research are children in Group B Satu Atap Kramat Jati 25 East Jakarta there are 10 children. The steps of this research : 1) Planing (2) Action (3) Observation (4) Reflection. Data analysis used quantitative and qualitative. Data analysis qualitative used Miles and Hubberman model. This research do in two cycles, there are cycle I and II. The end result of the overall analysis of the data is the percentage in 87,05% cycles II which showed from pre-cycle is 26,25% up to cycles I 55,52%. Keywords: Creation Dance, Self Confidence And Action Research